2012
DOI: 10.4319/lo.2012.57.6.1826
|View full text |Cite
|
Sign up to set email alerts
|

Viral lysis and microzooplankton grazing of phytoplankton throughout the Southern Ocean

Abstract: We investigated microzooplankton grazing and viral lysis of the pico-and nanophytoplankton community in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 37 publications
(89 reference statements)
6
26
1
1
Order By: Relevance
“…Although this observation might be a local or seasonal phenomenon, our findings are consistent with a smaller-scale study in the North Sea , which reported low viral lysis rates of picophytoplankton in offshore waters above 55°N. Furthermore, data from the Southern Ocean point at low viral lysis rates of phytoplankton over a relatively broad geographic range from at least 43°S to 70°S on the southern hemisphere (Evans and Brussaard, 2012). This suggests that low viral lysis rates at higher latitudes are not unique for our data set, but may represent a global pattern.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Although this observation might be a local or seasonal phenomenon, our findings are consistent with a smaller-scale study in the North Sea , which reported low viral lysis rates of picophytoplankton in offshore waters above 55°N. Furthermore, data from the Southern Ocean point at low viral lysis rates of phytoplankton over a relatively broad geographic range from at least 43°S to 70°S on the southern hemisphere (Evans and Brussaard, 2012). This suggests that low viral lysis rates at higher latitudes are not unique for our data set, but may represent a global pattern.…”
Section: Discussionsupporting
confidence: 80%
“…Estimates of viral lysis rates of natural phytoplankton populations remain scarce, and consequently the importance of viruses in comparison with other loss factors remains unclear. Rates of viral-mediated mortality for Synechococcus (that is, 0.03-0.49 per day), picoeukaryotic phytoplankton (that is, 0-0.81 per day) and nanoeukaryotic phytoplankton (that is, 0-1.05 per day) were comparable to the ranges reported in the literature (Baudoux et al, 2007Evans and Brussaard, 2012;Tsai et al, 2012). The viral lysis rates of Prochlorococcus (that is, 0.02-0.57 per day) presented here were higher than the maximal 0.06 per day reported thus far (Baudoux et al, 2007).…”
Section: Discussionsupporting
confidence: 73%
“…However, while mixed‐layer stocks of new iron appear more akin to a static inventory with little day‐to‐day change in their magnitude [ Croot et al , ], that from the recycled iron inventory is more dynamic as it is being “heavily trafficked” [ Morel and Price , ; Nuester et al , ] and hence shuttled around on timescales of hours [ Poorvin et al , ; Strzepek et al , ]. The timescales of iron recycling are inextricably linked to the turnover times of much of the microbial and planktonic populations, as the main modes of recycling involve grazing and viral lysis [ Boyd et al , ; Evans and Brussard , ; Matteson et al , ]. Based on the partitioning of biotic iron, much of this total biotic iron pool is associated with these small, rapidly turned over cells and/or their grazers (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Our present understanding of phytoplankton diversity and productivity in the WG, and Southern Ocean in general, is based upon bottom‐up rather than top‐down processes, in spite of the importance of grazing in the polar carbon cycle (le Quéré et al, ; Smetacek et al, ). Field experiments indicate that viral lysis of phytoplankton (both picoplankton and nanoplankton) can be relatively minor in the WG, while grazing by microzooplankton exerts significant control of phytoplankton growth (Agustí & Duarte, ; Evans & Brussaard, ; Froneman & Perissinotto, ; Henjes et al, ; Jacobsen et al, ). In contrast, larger zooplankton are of secondary relevance in controlling phytoplankton biomass (Garcia et al, ).…”
Section: Biology I: Phytoplankton Of the Wgmentioning
confidence: 99%